ANALISIS MUTASI GENA PENYANDI CORE PROMOTER VIRUS HEPATITIS B PADA PENDONOR DARAH DENGAN INFEKSI HEPATITIS B TERSAMAR DI UNIT PELAYANAN TRANSFUSI DARAH RSUP Dr. SARDJITO - , AGUNG PANJI WIDIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
BackgroundHepatitis B infection still becomes a global medical problem with high morbidity and mortality levels. Indonesia itself has medium to high endemicity level. Nowadays the occult hepatitis B infection appears which is marked by negative HBsAg but positive DNA VHB. On the other hand, low concentration of DNA VHB under cut-off point can also imply this occult infection. Some previous results show that core promoter mutation is connected with low virus concentration. ObjectiveIdentifying core promoter mutation and measuring virus concentration that has core promoter mutation. MethodSerum is separated from blood sample and tested with HBsAg, anti-HBs, and anti-HBc. All samples are extracted and amplified by PCR, then read by using electroforesis. We perform sequencing to the sample that positively has DNA VHB and virus concentration is measured by quantitative RT-PCR. ResultFrom 150 negative HBsAg samples there is positive anti-HBs 21,3%, and positive anti-HBc 33,3%. The result of electroforesis and sequencing is that there exists 18 samples of positive DNA VHB (12%), where there is core promoter mutation in 7 samples (38,9%). There is core promoter mutation in 5 samples of A1762T / G1764A (71,4%) and 2 samples of T1753C (28,6%). The average concentration of virus with core promoter mutation that can be detected is 2,2 log copies. This value is considered as low (under 2,5 log copies) and the virus concentration of some samples cannot be detected because it is under cut-off point 1,8 log copies. ConclusionThere iscore promoter gene mutation where its mutation is located at A1762T / G1764A and T1753C where the average of detected virus concentration is 2,2 log copies.